Modeling crosstalk effects of hybrid copper carbon nanotube interconnects using a novel accurate FDTD based method. (November 2022) - Nadir, Youssef; Belahrach, Hassan; Ghammaz, Abdelilah; Naamane, Aze-eddine; Radouani, Mohammed
Abstract: In the modern era of nano-electronics, the performance of Cu interconnects degrades with the technology node advancement, thus the hybrid copper carbon nanotubes (Cu-CNTs) have motivated researchers to use them as copper substitutes. Especially, the Cu-CNT line presents a better immunity to the crosstalk in comparison to Cu and CNT interconnects. In this way, an accurate FDTD based method has been developed and validated by the PSPICE results for the crosstalk effect analysis of coupled Cu-CNT interconnect lines at 22 nm and 14 nm technology nodes. The results achieved in this work employing the proposed method have shown better performance compared with the conventional FDTD and more accurate results compared with PSPICE. The simplicity, and accuracy of using the proposed model ensure several applications in the VLSI design tools.